Agriculture Towards 2030: Changes in Urbanization and Farm Size - Concept Note - CGIAR Independent Science and Partnership Council (CGIAR Independent Science and Partnership Council, 2012)
The next two decades will see continuing and dramatic changes in world food systems. This concept note is intended to point the way towards a systematic study of the ways in which some major trends and issues are likely to impact the international public research system, with specific relevance for the research portfolio of CGIAR and its partners.